Analysis Of Patterns, Differences And Relationships Between Mental Health Information Search And Phsical Activity Information In Indonesia - Tjahyo Kuntjoro, Bambang Ferianto; Junaedi, Mahbub (STAMINA, 2025)
The high cases of mortality and mental disorders during the COVID-19 pandemic have led to a phenomenon of health information-seeking behavior as an effort to maintain quality of life. This study aims to examine the patterns, differences, and relationships between searches for mental health information and physical activity information in Indonesia over the past 85 months (January 2018–January 2025). A cross-sectional study design with descriptive statistical tests, Kruskal-Wallis, and Spearman rank correlation was applied to analyze Google Relative Search Volume (RSV) data from various search terms in the categories of mental health (stress, anxiety, depression) and physical activity (running, weight training, boxing, camping). The results indicate that public interest in mental health information and physical activity information has increased based on the average RSV during the COVID-19 pandemic, except for boxing information. The Kruskal-Wallis test revealed significant differences in RSV between the search terms tested (p<0.05), with ‘anxiety’ (rank sum=36503) and ‘stress’ (rank sum=35288) being the most popular search terms over the past 85 months. Meanwhile, the Spearman rank test showed a significant positive correlation (p<0.05) between all mental health-related search terms (stress, anxiety, and depression) and the search term 'running' with a moderate correlation, as well as 'weight training' with a moderate to strong correlation. This study contributes to understanding the high public interest in mental health issues, which is connected to the search for information on running and weight training as potential therapies practiced by the public